Phenotypic consequences of somatic mutations in the ataxia-telangiectasia mutated gene in non-small cell lung cancer - Weber, A; Drobnitzky, N; Devery, A; Bokobza, S; Adams, R; Maughan, T; Ryan, A (Impact Journals, 2016)
Mutations in the Ataxia-telangiectasia mutated (ATM) gene are frequently found in human cancers, including non-small cell lung cancer (NSCLC). Loss of ATM function confers sensitivity to ionising radiation (IR) and topoisomerase inhibitors and may thus define a subset of cancer patients that could get increased benefit from these therapies. In this study, we evaluated the phenotypic consequences of ATM missense changes reported in seven NSCLC cell lines with regard to radiosensitivity and functionality of ATM signalling. Our data demonstrate that only 2/7 NSCLC cell lines (H1395 and H23) harbouring ATM missense mutations show a functional impairment of ATM signalling following IR-exposure. In these two cell lines, the missense mutations caused a significant reduction in ATM protein levels, impairment of ATM signalling and marked radiosensitivity. Of note, only cell lines with homozygous mutations in the ATM gene showed significant impairment of ATM function. Based on these observations, we developed an immunohistochemistry-based assay to identify patients with loss or reduction of ATM protein expression in a clinical setting. In a set of 137 NSCLC and 154 colorectal cancer specimens we identified tumoral loss of ATM protein expression in 9.5% and 3.9% of cases, respectively, demonstrating the potential utility of this method.